2022
DOI: 10.3389/fphar.2022.984555
|View full text |Cite
|
Sign up to set email alerts
|

SLC11A1 associated with tumor microenvironment is a potential biomarker of prognosis and immunotherapy efficacy for colorectal cancer

Abstract: Colorectal cancer (CRC) is one of the most lethal cancers of the digestive system. The tumor microenvironment (TME) plays a central role in the initiation and development of CRC. However, little is known about the modulation mechanism of the TME in CRC. In our study, we attempted to identify a biomarker related to the TME modulation that could serve as a potential prognostic biomarker for CRC. We identified differentially expressed genes between the ImmuneScore high/low and StromalScore high/low groups. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…These reports suggest that the model based on these genes may reflect various statuses of colorectal cancer. It is notable that the genes were immunerelated genes, according to MSigDB, and SLC11A1 was reported to be associated with the microenvironment (Ma et al, 2022) in CRC and a similar result was found for CASP6 in gliomas (Guo et al, 2022). The other genes were also reported to reflect or influence the immune status of various types of cancers (Boggio et al, 2022).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…These reports suggest that the model based on these genes may reflect various statuses of colorectal cancer. It is notable that the genes were immunerelated genes, according to MSigDB, and SLC11A1 was reported to be associated with the microenvironment (Ma et al, 2022) in CRC and a similar result was found for CASP6 in gliomas (Guo et al, 2022). The other genes were also reported to reflect or influence the immune status of various types of cancers (Boggio et al, 2022).…”
Section: Discussionmentioning
confidence: 63%
“…ICOS, SPFQ, and FSTL1 were also reported to be correlated with proliferation, cell adhesion, and prognosis ( Zhang et al, 2016 ; Gu et al, 2018 ; Meng et al, 2022 ), while the studies were focused on gene polymorphism of LEP and CASP6 ( Choi et al, 2012 ; Liu et al, 2014 ). Notably, SLC11A1 was reported as a potential biomarker for prognosis and immune therapy efficiency ( Ma et al, 2022 ). These reports suggest that the model based on these genes may reflect various statuses of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Both SLC11A1 and SLC2A3 are members of the solute carrier family and are responsible for encoding membrane transport proteins 50,51 . Reportedly, SLC11A1 not only predicts the prognosis of colorectal cancer and hepatocellular carcinoma 52,53 but also serves as a stratification indicator for immunotherapy or chemotherapy in glioma patients 54 . SLC2A3 exerts multiple biological functions in different cancers, including tumor EMT, ferroptosis, glycolytic reprogramming, drug resistance and immunity 55–59 .…”
Section: Discussionmentioning
confidence: 99%
“…SLC11A1, also known as natural resistance-associated macrophage protein-1, is a member of the lysosomal carrier family. It has been reported to be associated with a poor prognosis in various gastrointestinal tumours [ 49 ]. These potential biomarkers can enhance our understanding of molecular mechanisms and show promise as targets for future therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%